A parametric study of electrocoagulation as a recovery process of marine microalgae for biodiesel production - Uduman, N.; Bourniquel, V.; Danquah, Michael; Hoadley, A. (Elsevier BV, 2011)
Microalgal biomass as feedstock for biofuel production is rapidly gaining appreciation in response to the increasing petroleum prices and the upsurge in global warming concerns. However, the process of creating concentrated biomass from microalgal cultures is limited by ineffective dewatering procedures. The economics of existing culture clarification unit operations make the process of creating biomass from microalgae unattractive for biofuel development. This work involves the comparison of the removal efficiency (recovery) of two marine microalgae species Chlorococcum sp. and Tetraselmis sp. by electrocoagulation (EC), a technique that has not been thoroughly explored in marine microalgae dewatering. High recovery efficiencies were obtained of up to 99 and 98% for Tetraselmis sp. and Chlorococcum sp., respectively. The effect of culture temperature and salinity on removal efficiency was also observed. A starting temperature of 60°C resulted in optimal recovery values of 96 and 94% for Chlorococcum sp. and Tetraselmis sp., respectively. Whereas a starting temperature of 5°C achieved optimal recovery of only 5 and 68% for Chlorococcum sp. and Tetraselmis sp., respectively. Increased salinity of microalgae culture showed increased microalgae recovery. Salinity of 20% gave optimal microalgae recovery values of only 6 and 9% for Chlorococcum sp. and Tetraselmis sp., respectively. Zeta potential (ZP) analysis was carried out to verify and further understand the charge neutralization mechanism due to Fe2+ cations. © 2011 Elsevier B.V.